The Effect of Quality, Quantity and Work Motivation on Employee Performance of the Cirebon Regency Investment and One Stop Service (DPMPTSP) - Muhammad Fakri Goffar; Arin (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study — a study to find out about the quality, quantity and work motivation that affect the performance of employees at the Office of Investment and One Stop Integrated Services (DPMPTSP)Research method—This research is a quantitative research with regression. This study uses a quantitative approach to see the causal relationship of several factors that influence employee performance. The population in this study were the employees of the Regency Investment Office and PT. XYZ totaling 65 employees. Data were collected by questionnaire and document study, after which the data were tested for validity and reliability. Result—The results showed that Quality, Quantity and Work Motivation had an effect on employee performance simultaneously. The Multiple Determination Coefficient in this study uses the adjusted R square value because the independent variables in this study are more than 2 in estimating the influence of the two independent variables studied. From the adjusted R Square value data of 0.578, This means that together the influence of variables X1, X2, and X3 is 57.8% on variable Y or in other words the influence of independent variables (Quality, Quantity and Work Discipline) on the dependent variable (Performance) is 57.8% while the rest namely 42.2% caused by other variables that are not included in the research framework.